Pipe dreams; explaining the energy security policies of Poland, 1990-2007 - Zeniewski, P (2011)
This thesis seeks to explain Poland’s energy security policies towards Russia in the period from 1990-2007. It is inspired by the puzzle that Poland’s commitments to reduce its dependence on imported oil and gas from Russia have varied considerably during this period. Numerous large-scale projects to enhance energy security have been proposed, abandoned and revisited, all in the absence of a significant change to Poland’s level of dependence on Russia or its exposure to supply risks. This puzzle poses a challenge to conventional approaches to energy security, which tend to explain policies as a function of ‘material’ shifts in the price, supply or demand for fossil fuels. Though these factors are undoubtedly important it is argued that, in the case of Poland, energy security is more affected by domestic decision-making processes than by such material shifts. In particular, the degree and form of intervention in the energy sector by the political executive in Poland is highlighted as a key factor explaining energy security policy output. These interventions in Poland are classified and distinguished according to three types of ‘policy network’ – statist, corporatist and liberal, each of which represented a different outlook on the optimal means for ensuring energy security. These policy networks were embedded within different governments, and their preferences fashioned Poland’s responses to energy security challenges occurring under similar material conditions.